(untitled) (Research, Society and Development, 2020)
The aim of this study was to evaluate the antimicrobial and antioxidant activity of the essential oil and the hydroalcoholic extract of O. vulgare. For the extraction of the oil, the hydrodistillation technique was used with a Clevenger type apparatus and the extract was obtained by the maceration process in 70% ethanol. Phytochemical tests were performed showing the chemical classes present in the extract and essential oil. The evaluation of antimicrobial activity was performed using the disk diffusion technique, using strains of Escherichia coli (ATCC 25922), Salmonella sp. (ATCC 14028) and Staphylococcus aureus (ATCC 25923). The minimum inhibitory concentration (MIC), for each of the strains, was determined using the broth microdilution technique. In the analysis of antioxidant activity, the ABTS radical discoloration technique was applied. The essential oil of O. vulgare showed activity against all tested strains, the hydroalcoholic extract inhibited the growth of E. coli and Salmonella sp, but did not show activity against S. aureus. In the results obtained by the microdilution technique S. aureus showed the highest sensitivity with a MIC value of 150 µg / mL. No activity of hydroalcoholic extracts was verified by the microdilution technique at the tested concentrations. The antioxidant activity of the extract and essential oil was evidenced, with the best results observed for the extract.